PENGARUH MODEL MAKE A MATCH TERHADAP HASIL BELAJAR MATEMATIKA TENTANG PENYAJIAN DATA DIAGRAM LINGKARAN PADA SISWA KELAS VI SEKOLAH DASAR - Yustina Neny Hastuti; Wahyu Warastuti; Wiwin Kurniyanti; Nining Setyaningsih; Sumardi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
This research aims to analyze the influence of the Make a Match learning model on the mathematics learning outcomes of sixth grade elementary school students in the context of presenting data in circle diagrams. The research design used was a control group pre-test and post-test design, with research subjects 28 grade VI elementary school students 01 Anggrasmanis, who were divided into an experimental group (n=14) and a control group (n= 14). The results showed that the experimental group had a pre-test average of 60.71 and a post-test of 80.64, with standard deviations of 8.49 and 6.14 respectively. Meanwhile, the control group had a pre-test average of 61.43 and a post-test of 71.79, with standard deviations of 7.89 and 6.68 respectively. The t test showed that there was no significant difference between the pre-test scores of the two groups (p=0.813), but there was a significant difference in the post-test scores (p=0.001). Gain score analysis shows a more significant increase in learning outcomes in the experimental group (0.51) compared to the control group (0.27). It can be concluded that the Make a Match learning model has a significant influence on improving mathematics learning outcomes, especially in mathematics learning, circle diagram data presentation material for sixth grade elementary school students.